2010
DOI: 10.1073/pnas.1004604107
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lung tumor growth by complex pulmonary delivery of drugs with oligonucleotides as suppressors of cellular resistance

Abstract: Development of cancer cell resistance, low accumulation of therapeutic drug in the lungs, and severe adverse treatment side effects represent main obstacles to efficient chemotherapy of lung cancer. To overcome these difficulties, we propose inhalation local delivery of anticancer drugs in combination with suppressors of pump and nonpump cellular resistance. To test this approach, nanoscale-based delivery systems containing doxorubicin as a cell death inducer, antisense oligonucleotides targeted to MRP1 mRNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
151
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 167 publications
(155 citation statements)
references
References 32 publications
4
151
0
Order By: Relevance
“…Recently, we demonstrated that the efficacy of the chemotherapy can be substantially enhanced if both resistance mechanisms are simultaneously suppressed when an anticancer agent(s) is delivered. (3)(4)(5) We also showed that antisense oligonucleotides (ASO) and small interfering RNA (siRNA) can be efficiently used to suppress both types of resistance. (6)(7)(8) However, ASO and siRNA poorly penetrate cancer cells, are unstable in the bloodstream, and therefore require a special carrier system to preserve their activity in the extracellular environment and increase their accumulation in cancer cells.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we demonstrated that the efficacy of the chemotherapy can be substantially enhanced if both resistance mechanisms are simultaneously suppressed when an anticancer agent(s) is delivered. (3)(4)(5) We also showed that antisense oligonucleotides (ASO) and small interfering RNA (siRNA) can be efficiently used to suppress both types of resistance. (6)(7)(8) However, ASO and siRNA poorly penetrate cancer cells, are unstable in the bloodstream, and therefore require a special carrier system to preserve their activity in the extracellular environment and increase their accumulation in cancer cells.…”
mentioning
confidence: 99%
“…(11) When it comes to anticancer drugs, inhalation delivery would enhance the accumulation of anticancer agent(s) in the lungs with tumor and reduce severe toxic side effects on healthy tissues. (5) Inhaled drugs are commonly used by patients with asthma and chronic obstructive pulmonary disease. (12) Although some chemotherapeutic agents can be delivered through the pulmonary or intratracheal route, (13)(14)(15)(16) most anticancer drugs, as well as resistance suppressors ASO and siRNA, cannot be inhaled in their traditional form and require a special drug carrier system (DCS).…”
mentioning
confidence: 99%
See 3 more Smart Citations